Rancang bangun smart door double lock menggunakan sensor RFID dan piezoelektrik dengan home security detector berbasis IoT - Cahyani, Ningrum Ayu; Hartono, Hartono; Pratiwi, Umi (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2024)
As science and technology advance, traditional locks are increasingly considered inefficient. Traditional keys are not only vulnerable to break-ins, but also easy to copy and impractical. The shortcomings of traditional locking systems can be overcome by switching to digital locking systems. Researchers have designed and built a smart double locking system for doors that can be accessed via the rhythm of knocking and the NUID of the RFID tag. The door locking system can also be accessed through an Android smartphone based on IoT technology. In addition, this smart double door lock can also detect intrusion and instantly send notifications of abnormal situations to the user's mobile phone. The research was conducted in four stages: preparation, system design, system development, and system testing to characterize the system. To create a suitable system, the system design phase is divided into several types of diagrams and system designs, including block diagrams, circuit diagrams, schematics, 3D prototype design, and IoT technology interface design. In this research, the system was successfully built and can run with static characteristics of 0% error and 100% accuracy, so it can be said that the system is working well. The power requirement in the active standby state was 1,788W to 2,652W, and the electrical power demand when the system is actively working for ±6 seconds is 6.960 W - 8.016 W.